2018
DOI: 10.1371/journal.pone.0202690
|View full text |Cite
|
Sign up to set email alerts
|

Feedback of action outcome retrospectively influences sense of agency in a continuous action task

Abstract: Here, we investigated whether explicit feedback on the result of the action (success or failure) modified sense of agency (SoA) in a continuous action task. Participants carried a white dot with a delay to a target square while avoiding obstacle squares. The color of the target changed unpredictably between white and blue. A trial was considered as successful or failed if the dot reached the target while it was white or blue. Thus, actions during the task resulted in almost identical experiences of successful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…In this way, it was inferred how control during reaching may facilitate or inhibit agency of the terminating action of grasp and performance of the reach itself. Previous studies have shown the direct link of agency between continuous movements and terminal events (Wen et al, 2015;Oishi et al, 2018). In this study, we prioritized and considered implicit agency by time-interval estimation as a less biased (more sub-conscious) perceptive measure.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, it was inferred how control during reaching may facilitate or inhibit agency of the terminating action of grasp and performance of the reach itself. Previous studies have shown the direct link of agency between continuous movements and terminal events (Wen et al, 2015;Oishi et al, 2018). In this study, we prioritized and considered implicit agency by time-interval estimation as a less biased (more sub-conscious) perceptive measure.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the participants were at times asked to tap twice in given trials, which was also not a common design to examine SoA. Most studies have adopted a design in which participants press a button once as an action (Sato & Yasuda, 2005) or many times to control objects (Oishi et al, 2018(Oishi et al, , 2019. Taken together, future studies using other illusions but with a simpler design (e.g., within a single modality or action) are necessary to support the present results and strengthen the underlying mechanism of how perception of effect-related signals influence SoA production.…”
Section: Discussionmentioning
confidence: 99%
“…The effects can be simply a colored circle and a pure tone (e.g., Sato & Yasuda, 2005). In addition to the typical effects, some studies have used stimuli with affective valence (Wilke et al, 2012;Yoshie & Haggard, 2017), semantic feedback such as presentation of letters "success" or "failure" (Oishi et al, 2018(Oishi et al, , 2019, and fake feedback such as others' performance (Asai, 2015;Sirigu et al, 1999;Wegner et al, 2004). Operation of the effect presentation depends on contiguity, congruency, and contingency.…”
mentioning
confidence: 99%
“…Most studies using self-report measures found that positive compared to negative action outcomes lead to increased sense of agency. This has been shown for different types of affective stimuli such as consonant/dissonant sounds (Barlas and Obhi, 2014 ; Barlas et al, 2017 ), emotional facial expressions (Gentsch et al, 2015 ), and performance feedback in gambling tasks (Kulakova et al, 2017 ; Herman and Tsakiris, 2020 ) or motor control tasks (Oishi et al, 2018 , 2019 ; Le Bars et al, 2020 ). The finding of increased sense of agency for positive action effects has been interpreted as part of a self-serving bias in human cognition (Gentsch and Synofzik, 2014 ; Haggard, 2017 ).…”
Section: Does Affect Influence Sense Of Agency?mentioning
confidence: 91%